2020
DOI: 10.48550/arxiv.2009.14169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recent developments on quasineutral limits for Vlasov-type equations

Abstract: Kinetic equations of Vlasov type are in widespread use as models in plasma physics. A well known example is the Vlasov-Poisson system for collisionless, unmagnetised plasma. In these notes, we discuss recent progress on the quasineutral limit in which the Debye length of the plasma tends to zero, an approximation widely assumed in applications. The models formally obtained from Vlasov-Poisson systems in this limit can be seen as kinetic formulations of the Euler equations. However, rigorous results on this lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…The mean-field limit N → ∞ of the system (1.6) formally leads to the Vlasov-Poisson equation, as discussed above. Several authors [4,8,9,3,23,13,17,14,15,12,11] have considered the quasineutral limit of Vlasov-Poisson with varying assumptions on the initial datum. But in the monokinetic regime of present interest, Brenier [3] has rigorously shown that the quasineutral limit leads to the incompressible Euler equation (1.1).…”
mentioning
confidence: 99%
“…The mean-field limit N → ∞ of the system (1.6) formally leads to the Vlasov-Poisson equation, as discussed above. Several authors [4,8,9,3,23,13,17,14,15,12,11] have considered the quasineutral limit of Vlasov-Poisson with varying assumptions on the initial datum. But in the monokinetic regime of present interest, Brenier [3] has rigorously shown that the quasineutral limit leads to the incompressible Euler equation (1.1).…”
mentioning
confidence: 99%